1989
DOI: 10.1088/0953-8984/1/38/010
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasonic study of superconducting and non-superconducting GdBa2Cu3O7-x

Abstract: Detailed measurements are presented of ultrasonic wave velocity and attenuation in the orthorhombic, superconducting and the tetragonal, non-superconducting forms of GdBa2Cu30,-,. Theorthorhombicstate datadisplay asharpelastictransition at about 240 K which is absent from that of the tetragonal state; however, x-ray diffraction measurements show no evidence of a structural phase transition. The lattice thermal expansion is found to be fairly isotropic. The elastic response in the superconducting state is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…The  D for superconducting DyBa 2 Cu 3 O 7−␦ was 397 K and is comparable to acoustic Debye temperature values reported for other REBa 2 Cu 3 O 7−␦ superconductors [16,17,28]. The increase in absolute longitudinal and shear velocities at 80 K with x may be related to the decrease of cell volume as a result of substitution of smaller Sr 2+ (ionic radius: 1.25 Å) for Ba 2+ (ionic radius: 1.42 Å).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The  D for superconducting DyBa 2 Cu 3 O 7−␦ was 397 K and is comparable to acoustic Debye temperature values reported for other REBa 2 Cu 3 O 7−␦ superconductors [16,17,28]. The increase in absolute longitudinal and shear velocities at 80 K with x may be related to the decrease of cell volume as a result of substitution of smaller Sr 2+ (ionic radius: 1.25 Å) for Ba 2+ (ionic radius: 1.42 Å).…”
Section: Resultssupporting
confidence: 82%
“…Table 3. RE123 materials. Ultrasonic velocity measurements in oxygenated and oxygen depleted RE123 samples consistently demonstrated that step-like anomalies above 200 K disappeared after oxygen reduction confirming the oxygen related character of the anomaly [16,17,28,42]. Nevertheless, previous ultrasonic report on differently annealed Gd1113 samples which is isostructural to RE123, indicates that oxygen content is not the key factor influencing the anomaly [43].…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations